St. Kitts and Nevis electoral reform process : report ([s.n.] [S.l.], 2007)
Reports on information gathered that is deemed useful in the government's effort to reform the St. Kitts and Nevis Electoral System. Indicates that this information gathered drove home the point that meaningful reforms of the election system will require amendments to both the constitution and the ordinary election legislation.
Bibliography: p. 62